Solusi numerik model matematika SHEIR pada penyebaran penyakit campak dengan vaksinasi Dan kekebalan kelompok - Darmawati darmawati (SAINTIFIK, 2021)
In this paper, mathematical model of measles transmission dynamics considering vaccination and herd immunity is discussed. The solution of the model is investigated using euler, atangana, dan nonstandard finite difference method. After comparing the solutions of the model, we observe that the solutions obtained by using euler and atangana method diverge for certain step. On the other hand, the solutions obtained by using nonstandard finite difference always converge.